1980
DOI: 10.2307/1129535
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Aggression: A Rejoinder and Reprise

Abstract: A meta analysis of observational studies of peer-directed aggression by children aged 6 and younger yields a highly significant sex difference. Out of 32 studies, z values reflected higher male aggression in 24, no difference in 8, higher female aggression in none. Furthermore, boys' aggression is most often displayed in the presence of male partners. Evidence is presented that the sex difference is probably not merely an artifact of higher rates of male activity or social interaction. Existing cross-cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
141
2
8

Year Published

1985
1985
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 339 publications
(167 citation statements)
references
References 52 publications
9
141
2
8
Order By: Relevance
“…Presented at the Conference on Research on Disci¬ pline: The State of the Art, Deficits, and Implications, Chapel Hill, NC, April 25,1996 …”
mentioning
confidence: 99%
“…Presented at the Conference on Research on Disci¬ pline: The State of the Art, Deficits, and Implications, Chapel Hill, NC, April 25,1996 …”
mentioning
confidence: 99%
“…However, where a friendship is increasing over time, aggression increases too [Attili, 1984bl. Boys are more aggressive than girls [Omark and Edelman, 1975;Smith and Green, 1975;Whiting and Whiting, 1975; see review by Maccoby and Jacklin, 1974, 19801 but the difference depends not only upon the type of aggression shown [Manning, in press], but also upon the sex of both the actor and the partner, both in dyads and in peer groups [Abramovitch et al, 1979;Barrett, 1979;Hoving et al, 1974;McGrew, 1972;Smith and Green, 19751. I do not agree with Parke and Slaby [ 19831 who point out that the evidence for sex differences in both verbal and physical aggression-as reported by Maccoby and Jacklin ( 1980)-challenges traditional assumptions f Feshbach, 19701 that sex differences in aggression depend mainly on differences in the type of aggression displayed. My interpretation is that verbal and physical aggression can represent the same type of aggression.…”
Section: Relationship Between Actor and Target: Sex Differencesmentioning
confidence: 57%
“…Sex differences have been found, in fact, in the different forms of aggression. Maccoby and Jacklin (1980) stress the similarities in types of aggression between men and animals and the sex differences related to the different forms of aggression. They suggest that children's rough and tumble play, threats and agonistic encounters which occur in the context of contests over dominance primarily in male-male dyads, could resemble the type of male-male aggression occurring among animals.…”
Section: Relationship Between Actor and Target: Sex Differencesmentioning
confidence: 97%
“…Numerous studies have found that men behave physically more aggressively than women (Bettencourt & Miller, 1996;Eagly & Steffen, 1986;Frodi et al, 1977;Hyde, 1984;Knight et al, 1996;Maccoby & Jacklin, 1974, 1980 and men commit most homicides (Burbank, 1987;Buss & Shackelford, 1997;Fry, 1998;Daly & Wilson, 1988;Kellermann & Mercy, 1992). Characteristic of the homicides committed by men is that the victim is a male stranger or acquaintances (not close relationship) (Jurik & Winn, 1990;Kellerman & Mercy, 1992;Robbins et al, 2003), the motive is to defend one's status or honor (Buss & Shackelford, 1997;Polk, 1999), and jealousy (Buss & Shackelford, 1997;Daly & Wilson, 1988), whereas homicides committed by women are usually directed towards other family members (close relationship), and their motive is most frequently self-defense (Campbell, 1993;Daly et al 1982;Dobash et al, 1992;Jurik & Winn, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for sex differences in aggression have been explained, by biological predisposition (e.g., testosterone levels), social learning, reactions to provocation, patriarcal attitudes, sex roles, and types of aggression (Bandura, 1973;Berkowitz, 1989;Archer, 1991;Baillargeon et al, 2007;Maccoby & Jacklin, 1974, 1980Knight et al, 2002;Bettencourt & Miller, 1996). The sex differences in aggression have also been explained with evolutionary models, such as "sexual selection" and "differential male-female parental investment" (Daly & Wilson, 1988).…”
Section: Introductionmentioning
confidence: 99%